2011
DOI: 10.1007/s11060-011-0662-x
|View full text |Cite
|
Sign up to set email alerts
|

The nonsteroidal anti-inflammatory drug celecoxib suppresses the growth and induces apoptosis of human glioblastoma cells via the NF-κB pathway

Abstract: Gliomas are devastating primary tumors of the central nervous system and tend to recur even after standard therapy. Celecoxib, the selective COX-2 nonsteroidal anti-inflammatory drug, has anti-neoplastic activity against several malignancies. Accumulating evidence suggests that several COX-2-independent mechanisms may also be involved in the anti-tumor effects of celecoxib. Deregulation of the NF-jB signaling pathway contributes to enhanced glioma cell survival, proliferation, and chemoresistance. In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 47 publications
3
37
0
Order By: Relevance
“…The cycloxygenase-2 (COX-2) selective NSAIDS such as celecoxib (Celebrex™) and the now discontinued rofecoxib (Vioxx™) are treatments of for patients with RA. Celecoxib also has well known anti-cancer properties [30-33] and RA patients treated with celecoxib or rofecoxib have a lower risk of breast, prostate and colorectal cancers [34;35]. However, although there is no doubt that celecoxib is an excellent inhibitor of COX-2 there is much debate over its COX-2 independent activities and if these could play a role in its anti-inflammatory and anti-cancer effects [36-39].…”
Section: Discussionmentioning
confidence: 99%
“…The cycloxygenase-2 (COX-2) selective NSAIDS such as celecoxib (Celebrex™) and the now discontinued rofecoxib (Vioxx™) are treatments of for patients with RA. Celecoxib also has well known anti-cancer properties [30-33] and RA patients treated with celecoxib or rofecoxib have a lower risk of breast, prostate and colorectal cancers [34;35]. However, although there is no doubt that celecoxib is an excellent inhibitor of COX-2 there is much debate over its COX-2 independent activities and if these could play a role in its anti-inflammatory and anti-cancer effects [36-39].…”
Section: Discussionmentioning
confidence: 99%
“…Promising data have been reported, such as the ability of celecoxib (a COX-2 selective NSAID) to inhibit the proliferation of various glioblatoma cell lines in vitro [65] and to induce apoptosis via the NF-kB pathway. [66] In addition, several case control studies have suggested that NSAIDs reduce the risk for this aggressive brain cancer, but findings from a large prospective study did not support an inverse association between NSAIDs and risk of glioma and glioblastoma. [67] The NSAID sulindac has been reported to induce specific degradation of the Human papilomavirus oncoprotein E7 and to cause growth arrest (inhibition of the G1 to S transition of the cell cycle) and apoptosis in HeLa cervical carcinoma cells.…”
Section: Long-term Experimentsmentioning
confidence: 97%
“…In this context, the following agents should act to address the biology of ARMS by acting at genomic and proteomic levels: 1) Entinostat by virtue of its ability to: a) inhibit class I HDAC [32] and thereby, to interrupt the YY1-EZH2-HDAC1 inhibition of miR-29b2 and mir-29c allowing arrest of ARMS cell proliferation and promoting differentiation [1117, 28]; and b) its ability to effect direct transcriptional supression of PAX3:FOXO1 [33] and to inhibit the phosphorylative activation of PAX3—FOXO1 by polo-like kinase (PLK)1 [29, 34, 35]; 2) celecoxib inhibits the NF-kappaB pathway at multiple points [36] and should reduce the overproduction of YY1; 3) sulforaphane, a nutraceutical suppresses polycomb group protein level including EZH2 [37] and this should promote alveolar rhabdomyosarcoma's differentiation to a more benign form, induce apoptosis in the tumor cells [38] and reduce the survival of alveolar rhabdomyosarcoma leading to elimination of the tumor (in the latter study, sulforaphane was also shown to decrease the mRNA and protein levels of PAX3-FKHR, MYCN and MET in ARMS cells); 4) retinoic acid upregulates miR-214 which downregulates EZH2 protein in embryonic stem cells and miR-214-mediated EZH2 protein reduction accelerates skeletal muscle cell differentiation [39] (Both all-trans retinoic acid, ATRA and 9-cis retinoic acid suppressed the cell growth of alveolar rhabdomyosarcoma with evidence of a differentiating effect [40]. ATRA increased the expression of some genes associated with muscle differentiation and slowed the proliferation and promoted a more differentiated myogenic phenotype in ARMS cell lines [41].…”
Section: Discussionmentioning
confidence: 99%